Testing the Copernican principle by constraining spatial homogeneity - Valkenburg, Wessel; Marra, Valerio; Clarkson, Chris (Monthly notices of the Royal Astronomical Society. Letters, 2014)
Abstract. We present a new programme for placing constraints on radial inhomogeneity in a dark-energy-dominated universe. We introduce a new measure to quantif
Gesehen am 22.10.2020
Advance access publication 2013 November 18